Analisis Efektivitas Muhammadiyah Cabang Ciledug Kota Tangerang Dalam Proses Kaderisasi Keanggotaan - Arum Fatayan; Sartika Ayu; Aska Amalia Bachrudin (CV. Ulil Albab Corp, 2022)
Muhammadiyah is the largest Islam movement organization in Indonesia, as well as a renewal movement guided by the Al-Quran and Hadits. Muhammadiyah cadres arepeople who are elected as members to be responsible for leading Muhammadiyah. The purpose of this study was to find out and explore the process of regeneration at the Ciledug Branch of Muhammadiyah which was considered lacking in regeneration. Muhammadiyah Ciledug Branch is quite active in regular Muhammadiyah study activities. This study uses qualitative research methods to collect data from the Ciledug Branch Manager.Tangerang City through interviews, observations, and documentation. In the results of this study, it turned out that the Muhammadiyah Ciledug Branch was sufficient in membership regeneration, through business charity, routine studies were able could be agents of enewal in improving the quality of cadre membership of Muhammadiyah Ciledug Branch, Tangerang City though business charities.